Ginsenoside Rb1 Alleviates Bleomycin-Induced Pulmonary Inflammation and Fibrosis by Suppressing Central Nucleotide-Binding Oligomerization-, Leucine-Rich Repeat-, and Pyrin Domains-Containing Protein Three Inflammasome Activation and the NF-κB Pathway - Liu J; Fan G; Tao N; Feng F; Meng C; Sun T (Dove Medical Press, 2022)
Jingjing Liu,1- 3 Guoqing Fan,1- 3 Ningning Tao,4 Feifei Feng,5 Chao Meng,1- 3 Tieying Sun1,2 1Department of Respiratory Medicine and Critical Care, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of China; 2Graduate School of Peking Union Medical College, Beijing, People's Republic of China; 3The MOH Key Laboratory of Geriatrics, Beijing Hospital, National Center of Gerontology, Beijing, People's Republic of China; 4Department of Respiratory & Critical Care Medicine, Shandong Provincial Hospital Affiliated to Shandong First Medical University, Jinan, Shandong, People's Republic of China; 5Department of Respiratory & Critical Care Medicine, The Second Hospital, Cheeloo College of Medicine, Shandong University, Jinan, Shandong, People's Republic of ChinaCorrespondence: Tieying Sun, Department of Respiratory Medicine and Critical Care, Beijing Hospital, National Center of Gerontology, Institute of Geriatric Medicine, Chinese Academy of Medical Sciences, Beijing, People's Republic of China, Tel +15153169108, Email suntieying@126.comPurpose: Idiopathic pulmonary fibrosis is a chronic and irreversible fibrotic interstitial pneumonia of unknown etiology and therapeutic strategies are limited. Emerging evidence suggests that the continuous activation of the central nucleotide-binding oligomerization-, leucine-rich repeat-, and pyrin domain-containing protein 3 (NLRP3) inflammasome is involved in the pathogenesis of pulmonary fibrosis. Ginsenoside Rb1 (G-Rb1) is the most abundant component in the traditional Chinese herb ginseng and has anti-inflammatory and anti-fibrotic activities. The purpose of this study was to explore whether G-Rb1 exerts anti-inflammatory and anti-fibrotic activities in vivo and in vitro by suppressing the activation of the NLRP3 inflammasome and NF-κB pathway.Methods: Forty-eight male C57BL/6 mice were randomly divided into four groups (n=12/group) as follows: control, bleomycin (BLM), BLM/G-Rb1, and G-Rb1. A pulmonary fibrosis model was developed via an intratracheal injection of BLM. Six mice from each group were euthanized on days 3 and 21. The degree of pulmonary fibrosis was examined by histological evaluation and assessing α-smooth muscle actin levels. THP-1 cells were differentiated into macrophages, and stimulated by lipopolysaccharide and adenosine triphosphate. Activation of the NLRP3 inflammasome and NF-κB pathway was determined by Western blotting. Interleukin-1 beta and interleukin-18 levels were measured by ELISA. MRC-5 cells were cultured in the conditioned medium of the treated macrophages, after which markers of myofibroblasts were determined by Western blotting.Results: G-Rb1 ameliorated BLM-induced pulmonary inflammation and fibrosis in mice, and suppressed NLRP3 inflammasome activation and the NF-κB pathway in lung tissues. Moreover, interleukin-1 beta secreted after NLRP3 inflammasome activation in macrophages promoted fibroblast differentiation. G-Rb1 inhibited lipopolysaccharide- and adenosine triphosphate-induced NLRP3 inflammasome activation in macrophages and disturbed the crosstalk between macrophages and fibroblasts.Conclusion: G-Rb1 ameliorates BLM-induced pulmonary inflammation and fibrosis by suppressing NLRP3 inflammasome activation and the NF-κB pathway. Hence, G-Rb1 is a potential novel therapeutic drug for idiopathic pulmonary fibrosis.Keywords: G-Rb1, pulmonary fibrosis, NLRP3 inflammasome, macrophages